Gliadin allergy manifested with chronic urticaria, headache and amenorrhea. (5th December 2011) - Mingomataj, Ervin Ç; Gjata, Enkelejda; Bakiri, Alketa; Xhixha, Fatmira; Hyso, Entela; Ibranji, Alkerta
Abstract : Gluten intolerance is an autoimmune enteropathy caused by heterogeneous mixture of wheat storage proteins. Malabsorption symptoms imply diarrhoea, abdominal pain/bloating and weight loss. This case describes a 22-year-old female subject, who had chronic headache, joint pain, urticaria and long period of amenorrhea. Skin prick tests revealed a sensitisation to α-gliadin, while neurological, gynaecological, endocrine and clinical-laboratory examinations did not justify the above-mentioned symptoms. Gluten-free diet resolved chronic symptoms and re-established the menstrual cycle, whereas a temporary gliadin daily diet re-exacerbated all clinical symptoms. Urticaria occurred 20 min and the chronic headache the next day after exposure to the gliadin-rich diet. In addition, the missing of the expected menstrual bleeding was observed. This case demonstrates that gliadin intake can induce malabsorption and 'idiopathic' neuronal or gynaecological symptoms.